Metabolic profiling by 1H NMR of ground beef irradiated at different irradiation doses. (May 2015) - Zanardi, Emanuela; Caligiani, Augusta; Palla, Luigi; Mariani, Mario; Ghidini, Sergio; Di Ciccio, Pierluigi Aldo; Palla, Gerardo; Ianieri, Adriana
Abstract: This work describes a metabolic profiling study of non-irradiated and irradiated beef (at 2.5, 4.5 and 8 kGy) using 1 H NMR and chemometrics. The assignment of all major NMR signals of the aqueous/methanolic extracts was performed. A comprehensive multivariate data analysis proved the ability to distinguish between the irradiated and non-irradiated beef. Classification trees revealed that three metabolites (glycerol, lactic acid esters and tyramine or a p -substituted phenolic compound) are important biomarkers for classification of the irradiated and non-irradiated beef samples. Overall, the achieved metabolomic results show that the changes in the metabolic profile of meat provide a valuable insight to be used in detecting irradiated beef. The use of the NMR-based approach simplifies sample preparation and decrease the time required for analysis, compared to available official analytical procedures. Highlights: The development of new techniques for the detection of irradiated food is advocated. A step forward in the metabolic profiling of irradiated beef is presented. 1 H NMR-based metabolomic is a promising tool to detect irradiated beef.